2022
DOI: 10.3389/fonc.2022.1024600
|View full text |Cite
|
Sign up to set email alerts
|

Targeting phase separation on enhancers induced by transcription factor complex formations as a new strategy for treating drug-resistant cancers

Abstract: The limited options for treating patients with drug-resistant cancers have emphasized the need to identify alternative treatment targets. Tumor cells have large super-enhancers (SEs) in the vicinity of important oncogenes for activation. The physical process of liquid-liquid phase separation (LLPS) contributes to the assembly of several membrane-less organelles in mammalian cells. Intrinsically disordered regions (IDRs) of proteins induce LLPS formation by developing condensates. It was discovered that key tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 131 publications
0
2
0
Order By: Relevance
“…Phase separation is a driving force to form molecular condensates and MLOs [ 35 , 36 ]. For example, the liquid-liquid phase separation (LLPS), a type of phase separation, plays important roles in the formation of molecular condensates with non-ordered structures.…”
Section: Molecular Mechanisms Of Dbhs Family Proteinsmentioning
confidence: 99%
“…Phase separation is a driving force to form molecular condensates and MLOs [ 35 , 36 ]. For example, the liquid-liquid phase separation (LLPS), a type of phase separation, plays important roles in the formation of molecular condensates with non-ordered structures.…”
Section: Molecular Mechanisms Of Dbhs Family Proteinsmentioning
confidence: 99%
“…Moreover, the relevant studies continuously revealed the correlation of LLPS with tumorigenesis and tumor development [ 13 , 14 ]. Several studies had reported the importance of LLPS in PCa treatment and progression [ 15 ]. Widely recognized, the resistance to anti-androgen therapy of patients with PCa might due to the androgen receptor (AR) mutations or splice variants restoring AR signaling [ 16 ].…”
Section: Introductionmentioning
confidence: 99%